Activated Platelet Rich Plasma as a New Treatment Modality for Cataract Disorders: In Vivo Study - Rachmat Hidayat; Patricia Wulandari (Sriwijaya Journal of Ophthalmology, 2022)
Introduction: Cataract is the main cause of visual impairment and vision loss in the world, where 33% of the world's population has decreased vision due to cataracts. This study aims to explore the role of platelet-rich plasma (PRP) in inhibiting the pro-inflammatory cytokine interleukin-1ß, thereby triggering tissue repair in cataract cases in vivo study. Methods: This study is an experimental study with a post-test-only approach with a control group design. A total of 30 rats (Rattus norvegicus) Wistar strain was included in this study (male, 150-200 g, 8-10 weeks). The rats were divided into 3 groups, P1 (the group that was not induced by cataract and not treated with platelet-rich plasma), P2 (the group that was induced by cataract and given 10 uL of intraocular saline injection), and P3 (the group that was induced by cataract and given an intraocular injection of platelet-rich plasma). Plasma 10 uL). Results: The results showed that the P3 group that received platelet-rich plasma treatment showed a significant decrease in IL-1B levels when compared to the P2 group with cataract induced but without PRP administration (p<0.05). Conclusion: Activated platelet-rich plasma has potential as a new therapeutic modality in cataract conditions through inhibition of chronic inflammatory response in vivo studies.